RANCANGAN MEDIA PEMBELAJARAN KOSA KATA (MUFRODAT) BAHASA ARAB BERBASIS GAME ANDROID - Mezan el-Khaeri Kesuma; Guntur Cahaya Kesuma; Dani Saputra (LPPM Universitas Muhammadiyah Kotabumi, 2021)
One of the technologies needed by educators is learning media. This media aims to make it easier for educators and students in learning progress. The benefits of this research include: (1) helping, facilitating, and motivating students in learning Arabic; (2) become a reference in the development of instructional media; and (3) input for further research. The type of research that the author uses is research and development (R&D) and this study using the learning design model of ADDIE (Analyse Design Development Implementation Evaluate). The application is expected to be developed again so that Arabic learning in general and Mufrodat Learning in particular, can be more effective and students can be more interested and easier to understand the more complete Mufrodat material so that it makes students not to be bored.